1992
DOI: 10.1111/j.1469-8986.1992.tb01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Prestimulation‐Induced Startle Modulation in Attention‐Deficit Hyperactivity Disorder and Nocturnal Enuresis

Abstract: Startle modulation was induced by prestimulation in 43, 6-11 year old boys with attention-deficit hyperactivity disorder (ADHD), 13 of whom were or had been enuretic, 17 age-matched enuretic boys, and 42 age-matched normal boys, using 60-ms and 120-ms prestimulation intervals and a 4000-ms continuous tone. There was a significant multivariate effect of enuresis on startle amplitude modulation. This effect was attributed primarily to the reduction of amplitude inhibition following the 120-ms prestimulation inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 66 publications
6
79
0
4
Order By: Relevance
“…27 Thus lowered PPI appears to occur among individuals who are subject to unfiltered and irrelevant sensory, cognitive and/or motor perceptions. 19,28 Recently, as compared with 23 sibling controls, PPI among 25 children with 22q11DS was 20% less; secondary analyses suggested that this decrement did not reflect developmental delay. 29 The Attention Network Test (ANT) assesses the efficiency of three relatively segregated brain networks responsible for fundamental aspects of visual attention, including Alerting, Orienting, and Executive functions.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…27 Thus lowered PPI appears to occur among individuals who are subject to unfiltered and irrelevant sensory, cognitive and/or motor perceptions. 19,28 Recently, as compared with 23 sibling controls, PPI among 25 children with 22q11DS was 20% less; secondary analyses suggested that this decrement did not reflect developmental delay. 29 The Attention Network Test (ANT) assesses the efficiency of three relatively segregated brain networks responsible for fundamental aspects of visual attention, including Alerting, Orienting, and Executive functions.…”
mentioning
confidence: 88%
“…14,15 Lowered PPI has been shown in children with disorders characterized by a failure of brain inhibitory mechanisms including Tourette's syndrome, 16 posttraumatic stress disorder, 17 fragile X syndrome, 18 and among males with nocturnal enuresis and co-morbid ADHD. 19 Lowered PPI has also been found in adults whose psychiatric syndromes are characterized by poor selective-inhibitory control of attention, including obsessive compulsive disorder, 20,21 panic disorder, 22 social phobia, 23 Asperger's syndrome, 24 Huntington's disease, 25 bipolar mania, 26 and schizophrenia. 27 Thus lowered PPI appears to occur among individuals who are subject to unfiltered and irrelevant sensory, cognitive and/or motor perceptions.…”
mentioning
confidence: 99%
“…Compared with matched controls, PPI is deficient in patients with schizophrenia (e.g., Braff et al 1978;Swerdlow et al 2006), Huntington's disease Valls-Sole et al 2004), obsessive-compulsive disorder (OCD) Hoenig et al 2005;Ahmari et al 2012), nocturnal enuresis (Ornitz et al 1992), Asperger's syndrome (McAlonan et al 2002), 22q11 syndrome (Sobin et al 2005), Kleinfelter syndrome (Van Rijn et al 2011), fragile X syndrome (Frankland et al 2004), blepharospasm (Gomez-Wong et al 1998, and Tourette syndrome (Castellanos et al 1996;Swerdlow et al 2001b).…”
Section: The Evolution Of Prepulse Inhibition As a Validated Animal Mmentioning
confidence: 99%
“…A number of psychiatric illnesses with manifested dysfunction in attentional mechanisms are hypothesized to involve pathology of the NE system (AstonJones et al, 1999). PPI deficits can be seen in many of these conditions including attention-deficit-hyperactivity disorder (ADHD), schizophrenia, and post-traumatic stress disorder (PTSD); interestingly, with ADHD, this PPI disruption is seen only with attended-to prepulses Castellanos et al, 1996;Grillon et al, 1996;Hawk et al, 2003;Ornitz et al, 1992). Thus, clarifying the nature of PPI modulation by NE may further our understanding of how this system regulates functions that are relevant to the information processing-related deficits observed in these illnesses.…”
Section: Introductionmentioning
confidence: 99%